Extracorporeal multiorgan support including CO2-removal with the ADVanced Organ Support (ADVOS) system for COVID-19: A case report. Issue 4 (April 2021) - Huber, Wolfgang; Lorenz, Georg; Heilmaier, Markus; Böttcher, Katrin; Sahm, Philipp; Middelhoff, Moritz; Ritzer, Barbara; Schulz, Dominik; Bekka, Elias; Hesse, Felix; Poszler, Alexander; Geisler, Fabian; et al.
A substantial part of COVID-19-patients suffers from multi-organ failure (MOF). We report on an 80-year old patient with pulmonary, renal, circulatory, and hepatic failure. We decided against the use of extracorporeal membrane oxygenation (ECMO) due to old age and a SOFA-score of 13. However, the patient was continuously treated with the extracorporeal multi-organ- "ADVanced Organ Support" (ADVOS) device (ADVITOS GmbH, Munich, Germany). During eight 24h-treatment-sessions blood flow (100–300 mL/min), dialysate flow (160–320 mL/min) and dialysate pH (7.6–9.0) were adapted to optimize arterial PaCO2 and pH. Effective CO2 removal and correction of acidosis could be demonstrated by mean arterial- versus post-dialyzer values of pCO2 (68.7 ± 13.8 vs. 26.9 ± 11.6 mmHg; p < 0.001). The CO2 -elimination rate was 48 ± 23mL/min. The initial vasopressor requirement could be reduced in parallel to pH-normalization. Interruptions of ADVOS-treatment repeatedly resulted in reversible deteriorations of pa CO2 and pH. After 95 h of continuous extracorporeal decarboxylating therapy the patient had markedly improved circulatory parameters compared to baseline. In the context of secondary pulmonary infection and progressive liver failure, the patient had a sudden cardiac arrest. In accordance with the presumed patient will, we decided against mechanical resuscitation. Irrespective of the outcome we conclude that extracorporeal CO2 removal and multiorgan-support were feasible in this COVID-19-patient. Combined and less invasive approaches such as ADVOS might be considered in old-age-COVID-19 patients with MOF.